Lead time performance in a internet product delivery supply chain with automatic consolidation - Cruz-Mejia, O. (Springer Verlag, 2018)
Internet sales have increased exponentially in the last decade. Much of the internet sales are of physical products in urban areas that require product delivery transportation with a tight delivery lead time. With this challenge, a new type of transportation services has been developed aiming to cope with a strict control of transportation lead time. In this paper, an internet product delivery service with customer orders that are multi-item as well as single item is simulated. We address specifically the mismatch between supply and demand when retailers for any reason are unable to estimate the configuration of multi-item orders. Three scenarios of demand patterns are simulated (demand as forecasted, lower than forecasted and higher than forecasted) using discrete-event simulation to look at the effect on transportation lead time. Results show the positive effect on the mismatch between demand and resource capacity which is expressed in higher number delayed delivery orders. The excess of capacity in the product delivery supply chain has not a positive impact on delivery time of orders as technically orders are not delivered before the multi-item components are not available. This leads to think that the excess of resources are not an element that add value to customers waiting for their orders. Â© 2017, Springer-Verlag GmbH Germany.